Superman smashes the Klan : the graphic novel - Yang, Gene Luen (DC Comics, 2020)
When a Chinese-American family moves to the suburbs of Metropolis, children Roberta and Tommy Lee struggle to fit in among their white neighbors. Tension escalates from racial slurs to a wooden cross set afire in their front yard by the Klan of the Fiery Kross. Superman steps in to put a stop to the crime, and teaches Roberta and Tommy to be proud of their heritage.